ONE WORLD, TWO MONEYS - P.Guzelian, Christopher (REVISTA PROCESOS DE MERCADO, 2021)
National politicians, confronted with unprecedented sovereign debt and declining demand for future sovereign bonds, may engage in financial repression in their homelands, while issuing joint sovereign bonds with other nations (“Political Money”). These steps may obscure from pollyannaish creditors the fact that the nations are unsustainably indebted.Simultaneously, some central bankers have proposed a stepwise process by which nations would transfer their sovereign gold and silver as “collateral” for their individual and joint sovereign debts to a central banker-run repository that would initially act as the world’s biggest escrow agent. This supranational escrow agent/repository could (1) handle the retirement of most individual and joint sovereign debt and (2) eventually take de facto ownership of pooled sovereign gold, such that the repository could itself issue a universal “gold-linked” (which is not the same as gold-backed) fiat currency (“Oligarch Money”). Oligarch Money eventually could replace all Political Money. Nations would become financially borderless, losing their distinct fiscal characters.The byproducts of Political and Oligarch moneys will be mass poverty and environmental damage. Only by cooperation between politicians and central bankers to limit sovereign fiscal spending and to re-tether national currencies to national stores of precious metals can these consequences be avoided. Keywords: Sovereign debt, Political Money, Oligarch Money. JEL Classification: B53; E02; E42; H50; H60; H81; K10.